Suspected Cannabis Vaping-Induced Pericardial Effusion - Nicole Maharaj MBBS; Steven Swarath MBBS; Rajeev Seecheran MBBS, MHA; Valmiki Seecheran MBBS, MSc; Naveen Anand Seecheran MBBS (MD) (SAGE Publishing, 2022)
Pericardial effusions refer to an excess accumulation of fluid within the pericardial cavity. The etiology is diverse, with most cases being idiopathic in nature. We report a case of suspected cannabis vaping-induced pericardial effusion in a 31-year-old South Asian patient, which was successfully managed with high-dose aspirin, colchicine therapy, and cannabis vaping cessation. Key Clinical Message: Clinicians should be aware of the possible cardiovascular complications of cannabis vaping.